CRIMINAL POLICIES: PREPARATIONS OF CRIMINAL ACTS AS AN OFFENSE IN THE INDONESIAN CRIMINAL CODE (KUHP) - Mukhlis R; Fitri Wahyuni (LPPM STIH Putri Maharaja, 2026)
The topic of preparations for criminal acts needs to be regulated in the new Criminal Code, as it is not explicitly addressed and is only mentioned in sections that regulate specific criminal acts. This study involved normative legal research, with qualitative analysis performed on data derived from secondary sources. To more successfully protect the public from the threat of serious criminal actions like terrorism, murder, treason, and others, regulations on the definition of criminal acts as offenses in the new Criminal Code were required. The only way in which preparations for criminal acts can be penalized is if the law explicitly provides for it. It implies that not all attempts at committing crimes can be punished; instead, only plans to commit crimes that are thought to pose a serious threat to public safety, law and order, or social welfare, such as preparations to commit murder, treason, or acts of terrorism, are eligible for punishment. The elements outlined in the law must be met before committing a criminal act. Thus, only behaviors that demonstrate a distinct and serious intention to commit crimes—such as setting up facilities, obtaining information, organizing activities, or carrying out similar activities intended to create the conditions for the commission of a crime—can be classified as preparation for crimes. Instead, all other behaviors related to criminal activity cannot be classified as preparation for criminal acts.